2022
DOI: 10.1063/10.0010119
|View full text |Cite
|
Sign up to set email alerts
|

A review of anomalous refractive and reflective metasurfaces

Abstract: Abnormal refraction and reflection refers to the phenomenon in which light does not follow its traditional laws of propagation and instead is subject to refraction and reflection at abnormal angles that satisfy a generalization of Snell’s law. Metasurfaces can realize this phenomenon through appropriate selection of materials and structural design, and they have a wide range of potential applications in the military, communications, scientific, and biomedical fields. This paper summarizes the current state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…In equation (1), where f is the operating frequency, P r and P a represent reactive power and active power, respectively, it can be observed that the bandwidth is positively correlated with active power. As the sheet resistance R increases, the absorption bandwidth becomes wider.…”
Section: Structure Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In equation (1), where f is the operating frequency, P r and P a represent reactive power and active power, respectively, it can be observed that the bandwidth is positively correlated with active power. As the sheet resistance R increases, the absorption bandwidth becomes wider.…”
Section: Structure Designmentioning
confidence: 99%
“…The artificial electromagnetic metasurface has gained widespread attention and applications due to its low cost and efficient control of electromagnetic wavefronts. The functionalities of electromagnetic metasurfaces include wavefront control with reflection and transmission capabilities, frequency-selective surfaces that modulate amplitude, and electromagnetic perfect absorbers that completely absorb incident waves [1][2][3][4]. A frequencyselective surface (FSS) is a two-dimensional periodically arranged array structure that exhibits different responses to electromagnetic waves of varying frequencies, polarizations, and incident angles.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials, artificially designed structural materials, are utilized to manipulate THz waves by exploiting their exceptional electromagnetic properties. Metamaterials have facilitated the realization of essential functionalities in the THz regime including holograms [4,5], vortex beam generators [6,7], metalenses [8][9][10], and perfect anomalous diffractors [11,12]. Moreover, metamaterials have emerged as a crucial platform for investigating and exploring THz nonlinear phenomena, propelling the field of nonlinear photonics [13].…”
Section: Introductionmentioning
confidence: 99%
“…[ 23,24 ] Many applications, such as holography, light‐based radars (lidars), virtual/augmented reality, and solar sail steering, also require the ability to reflect power in a specific direction with very high efficiency using thin platforms (e.g., metasurfaces). [ 22,25–31 ]…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] Many applications, such as holography, light-based radars (lidars), virtual/ augmented reality, and solar sail steering, also require the ability to reflect power in a specific direction with very high efficiency using thin platforms (e.g., metasurfaces). [22,[25][26][27][28][29][30][31] In this paper, we derive an analytical closed-form expression (Equation (10)) for the upper bound on the power reflected, in any direction and polarization, from a generic planar structure of thickness h that is made of a single material characterized by a complex scalar susceptibility χ. No prior assumption about the structural features and details of the optimal design is made, as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%